Slovenian expressive suffixes - Kavčič, Karin (Slovenski jezik, 2025)
This paper presents a typological classification of Slovenian expressive suffixes based on their formal properties. Our analysis builds on crosslinguistic research on expressive suffixation in Russian, Spanish, German, and Greek (Wiltschko and Steriopolo 2007; Steriopolo 2008, 2009, 2015, 2016; Steriopolo, Markopoulos, and Spyropoulos 2021). These studies demonstrate that the place and manner of attachment of expressive suffixes can be predicted from their meaning within each language, though crosslinguistic variation exists. For instance, in Russian, expres-sive suffixes conveying attitude function as morphological heads, whereas in Greek, they act as modifiers. Similarly, size suffixes behave as modifiers in Russian and Spanish but as heads in Greek and German. In this paper, we analyze a subset of Slovenian expressive suffixes, specifically attitude suffixes with a positive emotional connotation and size suffixes with diminutive meaning, focusing on their manner of attachment. Our findings indicate that Slovenian does not exhibit a one-to-one correlation between form and function, as both size and attitude suffixes can behave either as modifiers or heads. This demonstrates that variation in attachment patterns is not only a crosslinguistic phenomenon but also occurs within a single language.
Keywords: classification; diminutives (grammar); klasifikacija; manjšalnice; pripone; Slovenian language; slovenščina; suffixes